Prognostic value of HLA class I expression in patients with cutaneous melanoma and soft tissue sarcomas treated with cancer-testis antigens-based vaccine - Tatiana L. Nekhaeva; Aleksei V. Novik; Dmitry V. Girdyuk; Anna B. Danilova; Polina A. Savchenko; Alina V. Grigoryevskaya; Maria A. Nekrasova; Natalia A. Efremova; Andrey V. Orekhov; Irina A. Baldueva (Exploration of Medicine)
Aim: To assess the predictive and prognostic role of HLA class I expression in patients with melanoma (Mel), and soft tissue sarcomas (STS) treated with autologous dendritic cell vaccine (DCV) (CaTeVac). Methods: From 2009 to 2023, 277 patients with Mel (143), and STS (134), received DCV at the N.N. Petrov National Medical Research Center of Oncology in adjuvant (78.3% and 14.9%) and therapeutic (21.7% and 85.1%) setting. HLA-typing was performed using a polymerase chain reaction with sequence-specific primers (PCR-SSP). Progression-free survival (PFS) and overall survival (OS) grouped by the presence of HLA alleles or HLA association rules were assessed using the Kaplan-Meier method (medians of survival in the month are presented). Results: Higher OS (41.1 vs. 22.1, P = 0.026) and PFS (6.0 vs. 3.9, P = 0.045) were found in HLA-A heterozygous STS patients, while HLA-B homozygous patients showed better OS (36.4 vs. 87.2, P = 0.023). HLA-A heterozygous Mel patients showed lower PFS (8.3 vs. not reached, P = 0.013). Association rules analysis on HLA expression revealed 20 rules with high confidence, seven of which were associated with the survival. HLA-B*07 and HLA-C*07 (21.2 vs. 52.2), HLA-B*40 and HLA-C*03 (17.6 vs. 45.4), HLA-A*02 and HLA-B*07 and HLA-C*07 (16.8 vs. 47.0), HLA-A*02 and HLA-С*07 (17.6 vs. 41.1), HLA-B*40 and HLA-A*02 and HLA-C*03 (8.3 vs. 50.2) decreased OS in STS (P < 0.05). HLA-A*02 and HLA-B*07 and HLA-C*07 (3.2 vs. 6.0), HLA-B*40 and HLA-A*02 and HLA-C*03 (3.2 vs. 5.9) decreased PFS in STS patients (P < 0.05). HLA-B*35 and HLA-C*04 increased median OS in STS from 33.4 to 153.3 months. Conclusions: HLA class I phenotype has a different impact on the survival in Mel and STS patients. The association rules based on HLA coexpression may have prognostic and predictive value. Further investigations of these parameters are warranted (The Trial Registration Number: NCT05539677).